Nitrogen management effects on soil mineral nitrogen, plant nutrition and yield of super early cycle common bean genotypes - Adriano Stephan Nascente; Maria da Conceição Santana Carvalho; Leonardo Cunha Melo; Paulo Holanda Rosa (Acta Scientiarum. Agronomy, 2017)
This study was conducted to measure the effects of the timing of nitrogen fertilization (NF) on soil N-NH4+ and N-NO3-, macronutrient contents in the leaves and grains, and the grain yield of super early genotypes (SEG) of common bean. Field experiments were performed for four growing seasons in an Oxisol soil in Santo Antônio de Goiás, Brazil, using a randomized block experimental design in a split plot scheme. The plots were planted with common bean SEG, and the subplots were the NF timings, including a treatment without N fertilization. The available soil N with improved fertility and medium to high levels of organic matter were enough to meet the N demands of the common bean crop in order to achieve yields of up to 3,000 kg ha-1. Fertilization with N, regardless of the time of application, provided no increase in the yield components, grain yield and the N, P and K contents in the leaves and grains of the common bean SEG. The genotypes CNFC 15873 and CNFC 15875 had higher grain yields in the rainfed summer, and the genotype CNFC 15874 had higher grain yields in the irrigated winter growing season. It can be inferred that the use of common bean SEG, with life cycles ranging from 65 to 77 days, can be a promising technology, providing grain yields similar to the control (IPR Colibri).